Emphasising Self-Directed Learning in VET-Schools: Teachers' Convictions and Role Negotiations - Anna Keller; Patric Raemy (International Journal for Research in Vocational Education and Training, 2024)
Context: Accompanying learners in their increasingly self-directed learning is an important goal in the field of vocational education and training. With digitalisation, the traditional role of the teacher, characterized in terms of an arbiter and transmitter of knowledge, is in crisis. Besides teachers' task in instruction, other role aspects are coming to the fore, such as supporting learners in their self-directed learning. Words such as coach, mentor, and learning facilitator emphasize mentoring as a key component of the teacher’s role, but these are challenging to implement in practice.